IOT Based Real-Time Prototype Model for Smart Street Light Controller and Fault Detector - Dr.G.Lakshmi VaraPrasad, M. Nagaraju, Dr. K. Laksmi Prasad (International Journal of Advanced Science and Technology, 2020)
The primary contemplation in the gift area technology is Automation, Power intake and cost efficiency. Automation is envisioned to decrease man power with the assist of clever systems. Power saving is the primary attention all the time because the source of the energy(Thermal, Hydro etc.) have become dwindled due to numerous reasons. As we all recognise that electricity intake has accelerated loads and sources of power are restricted so so that it will meet the increasing demand of power use of renewable resources of strength is a need to. The task targets to explain a way for modifying street mild illumination with the aid of using sensors at minimal electrical electricity consumption. When presence is detected, all surrounding avenue lights glow at their brightest mode, else they stay inside the dim mode. LED bulbs shall be implemented as they may be higher than traditional incandescent bulbs in every manner. This shall reduce warmth emissions, electricity consumption, preservation and substitute charges and carbon dioxide emissions. Coupled with SSSLS (Solar Smart Street Light System), massive electricity-financial savings are anticipated. Also, an indication with a actual-time proto kind version related to costs and implementation manner has been advanced the usage of internet of factors (IoT) to visualise the actual time updates of street processing and notifying the adjustments arise.. Keywords: IOT, PIR SENSOR, TIR Sensor, Raspberry pi , Arduino.